Perluasan Jangkauan Pasar dan Peningkatan Keterampilan Pengolahan Pala melalui Pengembangan Jejaring Sosial UMKM Dapur Pala - Muhammad Ramdhani Al Azraq Syah Syah; Saadul Rijal; Tiara Putri Rahmadin; Tri Ratna Chaniyatun Nisa; Murdianto Murdianto (Institut Pertanian Bogor, 2025)
This program aims to increase partners' knowledge of effective marketing strategies and the importance of social networks. Through this approach, MSME partners will be introduced to product processing skills, especially nutmeg, which can be done independently by them. UMKM Dapur Pala, which produces processed nutmeg in Bogor Regency, has faced obstacles such as limited capital, difficulty managing exports, and a lack of digital marketing capabilities since it was founded in 2018. Through networking with educational institutions, research institutions, and the private sector, which have related experience, MSMEs can access useful resources and information. This will help them improve product quality, understand export markets, and strengthen digital marketing to reach a wider audience. The method for developing the Dapur Pala MSME network was conducted in a hybrid manner through initial visits, program delivery, STP incubation, partnership collaboration with various parties, and evaluation. Data were collected through interviews and document studies to identify partner needs. As for the results of this activity, Kitchen Nutmeg MSMEs were able to expand their network through involvement in the STP IPB Business Incubation, Ecology Corner, Kebun Merdesa, and IPB Agrianita Organization, proving the effectiveness of social network development in supporting the growth and sustainability of MSMEs in the nutmeg farming industry. For future suggestions, it is hoped that Dapur Pala MSMEs will continue to develop digital skills, utilize online platforms, and build sustainable partnerships to expand their market reach and increase their competitiveness.